Evaluasi penerapan standar akuntansi berbasis akrual pada Kabupaten Manggarai (Studi kasus pada Badan Keuangan Kabupaten Manggarai Kota Ruteng) - Diana Westi Jebian; Cindy Getah Trisna June (University of Merdeka Malang, 2020)
The purpose of this study was to determine the readiness of the Manggarai Regency Financial Agency as indicated by commitment, human resources, infrastructure and information systems, to find out the obstacles in the implementation of PP No. 71 of 2010, regarding government accounting standards (SAP) and to find out the strategy model to face obstacles in the implementation of PP no. 71 of 2010 concerning accrual-based government accounting standards (SAP). The type of research conducted is descriptive qualitative. This research was conducted by taking the object at the Manggarai Regency Finance Agency which is located at Jl. Cathedral No. 3 Ruteng, flores. The types of data used in this research are primary data and secondary data. The data analysis method used descriptive analysis. Based on the previous data analysis, the readiness of the Manggarai Regency Financial Agency indicated by commitment, human resources, infrastructure, and information systems, it can be concluded that BKKM viewed from the integrity/commitment parameters is a very ready category, and for the readiness of human resources, infrastructure and information systems is the category ready. The strategy model faces obstacles in implementing PP N0. 71 of 2010 concerning accrual-based SAP is by providing technical guidance and training related to accrual-based SAP and adding a computer network that is already systemically using the SIMDA program.